Organizational Diagnostic Model in Higher Education: Literature Review of Organizational Diagnostic Model through Mckinsey 7s Framework Model, Weisboard 6 Boxes Model and National Education Standards in Indonesia - ., Sasmoko; Indrianti, Yasinta; Widhoyoko, Anindyo; Wahab, Rochmat (International Journal of Engineering and Technology, 2018)
Organizational diagnosis is done for organizational development and change. This study aims to further examine the concept of an organizational model that tries to cultivate the McKinsey 7S Framework Model and the Weisbord Six Box Model with the National Standards of Higher Education. This research uses Neuroresearch research method, which is a research method that combines quantitative and qualitative research with an exploratory stage. The result of the research shows the design of Organizational Diagnostic Model for Higher Education in Indonesia which consists of Strategy, Structure, System, Skill, Staff, Leadership, Value and Purpose (SNPT) consisting of Education Standard, Research Standard, and Standard of Community Service. Â